Given:
(x + 1)(x - 5) = -9
Let's select the correct statement from the given options.
Equate the equation to zero by adding 9 to both sides of the equation:
(x + 1)(x- 5) + 9 = -9 + 9
(x + 1)(x - 5) + 9 = 0
Expand the left side using FOIL method:
![x(x-5)+1(x-5)+9=0](https://img.qammunity.org/2023/formulas/mathematics/college/regmwvmpilrj58yvfnswer73ywlmk6ybbu.png)
Apply distributive property:
![x^2-5x+x-5+9=0](https://img.qammunity.org/2023/formulas/mathematics/college/5z8boav984msllyp4os2n8sp8owq6ytbey.png)
Combine like terms:
![x^2-4x+4=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/8s352v6t4ditgs3x4fz13nt8zu1bu3tapp.png)
Factor using the perfect square rule:
![\begin{gathered} x^2-2\ast x\ast2+2^2=0 \\ \\ (x-2)^2=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/mey1f8jr8t3phalfxzfvj1l9vp1rxg2ean.png)
Thus, we have the factor:
![x-2=0](https://img.qammunity.org/2023/formulas/mathematics/college/37bb8zimirpvp9nlxkkpzxonpgioid3lic.png)
Therefore, the correct statement is: x - 2 = 0
ANSWER:
x - 2 = 0